Resonant enhancement of the zero-phonon emission from a colour centre in a diamond cavity - Faraon, Andrei; Barclay, Paul E; Santori, Charles; Fu, Kai-Mei C; Beausoleil, Raymond G (Nature photonics, 2011)
Integrated quantum photonic technologies are key for future applications in quantum information1,2, ultralow-power opto-electronics3 and sensing4. As individual quantum bits, nitrogen-vacancy centres in diamond are among the most promising solid-state systems identified to date, because of their long-lived electron and nuclear spin coherence, and capability for individual optical initialization, readout and information storage 5-9. The major outstanding hurdle lies in interconnecting many nitrogen vacancies for large-scale computation. One of the most promising approaches in this regard is to couple them to optical resonators, which can be further interconnected in a photonic network. Here10-12, we demonstrate coupling of the zero-phonon line of individual nitrogen vacancies to the modes of microring resonators fabricated in single-crystal diamond. Zero-phonon line enhancement by more than a factor of 10 is estimated from lifetime measurements. The devices are fabricated using standard semiconductor techniques and off-the-shelf materials, thus enabling integrated diamond photonics. © 2011 Macmillan Publishers Limited. All rights reserved.